ANALISIS KEMAMPUAN KOGNITIF DAN KESULITAN BELAJAR SISWA PADA MATERI POKOK SISTEM PENCERNAAN MAKANAN DI KELAS XI IPA MAN DI KOTA MEDAN - Ummi Rapikah; Tri Harsono; Darusalim Darusalim; Herawati Herawati; Masdiana Masdiana (Jurnal Pelita Pendidikan, 2017)
This study aims to determine the level of student learning difficulties based on cognitive aspects on the subject matter digestive system food grade XI IPA MAN in the city of Medan learning year 2016/2017. Students' learning difficulties were obtained through questionnaires and validated tests, students with learning difficulties were students who scored below the KKM. The sample in this research is 118 people consisting of 48 0rang class XI Mia-6 MAN 1 Medan, 41 class XI IPA MAN 2 Model Medan and 29 class XI Mia-5 MAN 3 Medan taken by cluter random from population sample. Based on data analysis descriptively obtained level of student's learning difficulties on food digestive system material class XI IPA MAN in Medan city of learning year 2016/2017 Degree of student's learning difficulties in material digestive system of food in class XI IPA MAN in Medan city year of study 2016/2017 obtained The highest percentage of learning difficulty is found in Man 2 Field model is C1, C2, C3 aspect Including high C4 aspect category and C5 aspect is very high category, while in Man 3 Medan C1 aspect is high as aspect C2, C3, C4, C5 Imperative In the category of low and in Man 1 Medan entered in the moderate category.Based on data from the three schools can be seen that in Man 3 Medan internal factors are very influential as the cause of difficulty learning in the external factors influencing teachers, media and learning methods. In Man 2 Medan Model factors that are very influential only motivation, environment, media and learning methods used by teachers. And Man 1 Medan is only the motivation of the newcomers as the cause of student learning difficulties.Keywords: Learning difficulties